2020
DOI: 10.1007/s43154-020-00010-9
|View full text |Cite
|
Sign up to set email alerts
|

Societal and Ethical Issues in HRI

Abstract: Purpose of the Review The purpose of this review is to give an overview of the societal and ethical issues in human-robot interaction, (HRI), mainly focusing on the literature of the last five years. Recent Findings Both general ethical challenges associated with robot deployment and those specific to human-robot interaction are addressed and complemented by discussions of ethics within HRI research, ethics related behavior towards robots, as well as ethics and robot rights. Moreover, we discuss ethical challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 114 publications
0
12
0
Order By: Relevance
“…Surveying this area more broadly, the application of social robots within care settings, and as tools to deliver health and well-being interventions, is already an emerging success story highlighting contexts and uses where social robots are successfully being deployed as autonomous assistance tools for human users [82]. While it remains uncontroversial that social robots do not (yet) offer the same opportunities as humans for social interactions [33], they can nonetheless afford valuable opportunities for social engagement with human users when introduced in specific contexts, and in careful, ethically responsible ways [83,84]. A growing evidence base documents how social robots might function as autonomous tools to support psychological health interventions [42,85], physical therapy and physical health [86][87][88], and other means to amplify or support human therapeutic efforts (see [89•, 90]).…”
Section: Social Robots Deployed In the Wildmentioning
confidence: 99%
“…Surveying this area more broadly, the application of social robots within care settings, and as tools to deliver health and well-being interventions, is already an emerging success story highlighting contexts and uses where social robots are successfully being deployed as autonomous assistance tools for human users [82]. While it remains uncontroversial that social robots do not (yet) offer the same opportunities as humans for social interactions [33], they can nonetheless afford valuable opportunities for social engagement with human users when introduced in specific contexts, and in careful, ethically responsible ways [83,84]. A growing evidence base documents how social robots might function as autonomous tools to support psychological health interventions [42,85], physical therapy and physical health [86][87][88], and other means to amplify or support human therapeutic efforts (see [89•, 90]).…”
Section: Social Robots Deployed In the Wildmentioning
confidence: 99%
“…While it remains uncontroversial that social robots do not (yet) offer the same opportunities as humans for social interaction and engagement (22), their cognitive architectures and embodied cognition can nonetheless elicit socially meaningful behaviours from humans (69). As such, social robots can afford valuable opportunities for engagement with human users when introduced in specific contexts, and in careful, ethically responsible ways (83). A previous study reported that a social robot (NAO, SoftBank Robotics) was successful in eliciting rich disclosures from human users, evidenced in the information that was shared, people's vocal output, and their perceptions of the interaction (47).…”
Section: Overcoming Social Barriersmentioning
confidence: 99%
“…offer the same opportunities as humans for social interactions [33], they can nonetheless afford valuable opportunities for social engagement with human users when introduced in specific contexts, and in careful, ethically responsible ways [83,84]. A growing evidence base documents how social robots might function as autonomous tools to support psychological health interventions [42,85], physical therapy and physical health [86,87,88], and other means to amplify or support human therapeutic efforts (see [89,90] In contrast, health interventions where more active participation is required are finding that robots with a more human-like embodiment are more effective.…”
Section: Social Robots Deployed In the Wildmentioning
confidence: 99%